Prediction of the potential distribution area of Jacaranda mimosifolia in China under climate change using the MaxEnt model - Li, Xiaomei; Zhang, Guowu; Xie, Chunping; Qiu, Jianhuang; Liu, Xuefeng (Frontiers in Forests and Global Change, 2024)
Introduction Jacaranda mimosifolia, native to South America, is a notable ornamental tree widely used in Chinese urban landscaping due to its aesthetic and environmental value. Despite its popularity, the cultivation of J. mimosifolia in China faces challenges, including intermittent failures in various regions. This study assesses the potential distribution of J. mimosifolia in China and its response to climate change, providing insights for its application and promotion. Methods Using MaxEnt software, we developed an ecological niche model from 218 distribution records and selected 10 environmental variables to predict the tree’s distribution under various climate scenarios (SSP126, SSP245, SSP370). Results Our model demonstrates high predictive accuracy (AUC > 0.90) across scenarios, identifying key factors such as the mean temperature of the coldest quarter (bio11), precipitation of the driest month (bio14), temperature annual range (bio7), and minimum temperature of the coldest month (bio6). Their relative contribution rates were 49.3%, 18.4%, 15.6%, and 2.0%, respectively. The average temperature of the coldest quarter was not lower than 5°C, with the ideal range being 7.38 14.88°C. Currently, J. mimosifolia predominantly thrives in Taiwan, Fujian, Guangdong, Hainan, Guangxi, Yunnan, and to a lesser extent in the Sichuan Basin, southern Guizhou, Tibet, Hunan, Jiangxi, and Zhejiang province, covering a total area of approximately 122.19 × 104 km2. Future predictions indicate that under the SSP126 scenario, the most significant contraction occurs between the 2050s and 2070s, with a total change of −1.08 × 104 km2. Conversely, under the SSP370 scenario, the greatest expansion is observed from the 2030s to the 2050s, amounting to a change of 2.08 × 104 km2. Suitable area expansion is anticipated in most periods and scenarios, except for SSP126 in the 2070s, SSP245 in the 2050s, and SSP370 in the 2030s and 2070s. The distribution center shifts observed include movements northwestward, southwestward, and eastward with distances ranging from 5.12 km to 18.84 km. These shifts are likely driven by global warming, resulting in movements to higher elevations and latitudes. Discussion These predictions will provide a solid theoretical foundation for the future application of J. mimosifolia in urban landscaping and serve as a valuable reference for its introduction and cultivation.